2008
DOI: 10.1039/b812174e
|View full text |Cite
|
Sign up to set email alerts
|

Generation and reactivity of the dehydrotropylium-Co2(CO)6 ion

Abstract: Dehydrotropylium-Co(2)(CO)(6) ion (2) has been generated by the Lewis acid mediated ionization of alcohol (3); it is attacked by relatively strong nucleophiles (N>1), but undergoes a radical homocoupling in the presence of weak nucleophiles (N<1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Attempts to incorporate less reactive nucleophiles, with N < 1 (i.e., thiophene, N = −1.01), resulted in the formation of elimination product 14 , whereas radical homocoupling products were not seen in any of these reactions, in contrast to analogous reactions on dehydrotropylium–Co 2 (CO) 6 ion ( 2 ) precursors. 6…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to incorporate less reactive nucleophiles, with N < 1 (i.e., thiophene, N = −1.01), resulted in the formation of elimination product 14 , whereas radical homocoupling products were not seen in any of these reactions, in contrast to analogous reactions on dehydrotropylium–Co 2 (CO) 6 ion ( 2 ) precursors. 6…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, an allylic alcohol has been shown to successfully undergo MnO 2 oxidation to an enone in the presence of a non-reacting alcohol function (see Scheme 18). [33] In the same work, it was demonstrated that a β-hydroxycycloheptenone complex will undergo elimination to form the enone in the presence of HBF 4 or pTsOH (Scheme 18). For both oxidation and elimination reactions, it is likely that the full range of compatible reagents and conditions is yet to be explored.…”
Section: Oxidation/eliminationmentioning
confidence: 94%
“…[33] RCM adduct 29 underwent rearrangement in acid to give 30, which in turn afforded 31 by way of nucleophilic cleavage of the acetates and allylic alcohol oxidation. Elimination of the alcohol and reduction of the ketone gave the target alcohol 27.…”
Section: Ionmentioning
confidence: 99%
“…178 The substitution of a leaving group, such as propargylic acetate, with heteroatom-and carbon-based nucleophiles is highly chemoselective in that it avoids the formation of allenes. Recent investigations of heteroatom nucleophiles involve the formation of bispropargylic ethers, 179 cyclic polyethers, 180,181 propargylic azides, 182 dithia-and thia-oxacyclooctynes, 183 seven-and eight-membered cyclic ethers 184 and carbacycles [185][186][187] with a cobalt-protected triple bond as well as the formation of 5-alkynylproline derivatives. 188 The dicobalt hexacarbonyl moiety is able to stabilise cationic species which can be attacked by nucleophiles.…”
Section: Nicholas Reactionsmentioning
confidence: 99%